2015
DOI: 10.1016/j.pacfin.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

CFO compensation: Evidence from Australia

Abstract: We investigate the extent to which the incentive alignment theory and the managerial power theory explain the variability of CFO compensation in Australia. We find a positive relationship between the level of CFO compensation and measures of job complexity and firm stock market performance. However, we do not find the pay-for-performance link when performance is measured at the CFO-specific level. CFOs actually receive higher non-cash compensation when reporting quality is lower, suggesting a sharp contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 73 publications
3
27
0
Order By: Relevance
“…Lastly, Panel C provides summary statistics of all other firm‐specific, CEO‐specific and corporate governance control variables incorporated in the regression analysis. The results obtained are consistent with other contemporary empirical studies of corporate governance in Australia (see also Matolcsy and Wright, , ; Clarkson et al ., ; Monem, ; Monem and Ng, ; Duong and Evans, ).…”
Section: Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, Panel C provides summary statistics of all other firm‐specific, CEO‐specific and corporate governance control variables incorporated in the regression analysis. The results obtained are consistent with other contemporary empirical studies of corporate governance in Australia (see also Matolcsy and Wright, , ; Clarkson et al ., ; Monem, ; Monem and Ng, ; Duong and Evans, ).…”
Section: Empirical Analysismentioning
confidence: 99%
“… Termination payments, despite being made at the conclusion of employment should theoretically be amortised over the entire employment horizon of the CEO. Thus, by excluding final year payments, this decreases the likelihood of misrepresenting remuneration figures for individual executives (Merhebi et al ., ; Bushman et al ., ; Duong and Evans, ). …”
mentioning
confidence: 99%
“…() found that firms with well‐structured remuneration committees, more independent directors on the board and separation of the roles of CEO and board chair are more likely to grant options with longer time‐vesting features and performance hurdles. Duong and Evans () investigate the extent to which the incentive alignment theory and the managerial power theory explain the variability of CFO compensation in Australia. Xu et al .…”
Section: Previous Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Core et al, 1999;Bebchuk and Fried, 2004;Meherbi et al, 2006;Faleye et al, 2011;Bugeja et al, 2016;Duong and Evans, 2015), we control for CEO power, other board and firm characteristics that are known to affect CEO compensation. CEO power is proxied by four CEOrelated variables: CEO duality (DUAL), ownership (CEO_OWN), age (AGE) and tenure (TENURE).…”
Section: Measures Of Other Explanatory Variablesmentioning
confidence: 99%